Salmonella persisters promote the spread of antibiotic resistance plasmids in the gut - Bakkeren, Erik (Nature, 2019)
The emergence of antibiotic resistant bacteria by mutations or by acquisition of genetic material like resistance plasmids represents a major public health issue (1,2) (Extended Data Fig. 1a). Persisters are bacterial subpopulations surviving antibiotics by reversibly adapting their physiology (3–10). They promote the emergence of antibiotic resistant mutants (11). We asked if persisters can also promote the spread of resistance plasmids. In contrast to mutations, resistance plasmid transfer requires the co-occurrence of two different bacterial strains: a donor and a recipient (Extended Data Fig. 1a). For our experiments, we chose the facultative intracellular entero-pathogen Salmonella enterica serovar Typhimurium (S.Tm) and E. coli, a common microbiota member (12). S.Tm forms persisters surviving antibiotic therapy in several host tissues. We show that tissue-associated, S.Tm persisters account for long-lived reservoirs of plasmid donors or recipients. Persistent S.Tm reservoir formation requires Salmonella Pathogenicity Island (SPI) -1/2 in the gut-associated tissues or SPI-2 at systemic sites. Re-seeding of these bacteria into the gut lumen allows co-occurrence of donors with gut-resident recipients, thereby favouring plasmid transfer between various Enterobacteriaceae. We observe up to 99% transconjugants within 2-3 days after re-seeding. Mathematical modeling shows that rare re-seeding events may suffice for a high frequency of conjugation. Vaccination reduces tolerant reservoir formation after oral Salmonella infection and subsequent plasmid transfer. We conclude that even without selection for plasmid-encoded resistance genes, small persistent pathogen reservoirs can foster the spread of promiscuous resistance plasmids in the gut.